2015
DOI: 10.1007/s00467-015-3166-7
|View full text |Cite
|
Sign up to set email alerts
|

Novel factor H mutation associated with familial membranoproliferative glomerulonephritis type I

Abstract: Different mutations in CFH may be responsible for different glomerular diseases, including MPGN type I. A modifier gene or an environmental trigger may contribute to this phenotype-genotype discrepancy. Understanding the role of the alternative complement pathway in this disease would allow us to offer these patients more targeted therapy, including a clinical trial of eculizumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Two patients with homozygous CFH deficiency, the main regulatory protein of AP, have been diagnosed with Ig-MPGN. 10,11 C3Nef was positive in 50% of patients in two large Ig-MPGN cohorts. 4,12 Applying the current histopathologic definition of MPGN, ten of 14 patients in our series with available biopsy specimens were diagnosed as Ig-MPGN, because the C3 intensity of the staining evaluated by IF was identical to the other immune reactants.…”
Section: Discussionmentioning
confidence: 96%
“…Two patients with homozygous CFH deficiency, the main regulatory protein of AP, have been diagnosed with Ig-MPGN. 10,11 C3Nef was positive in 50% of patients in two large Ig-MPGN cohorts. 4,12 Applying the current histopathologic definition of MPGN, ten of 14 patients in our series with available biopsy specimens were diagnosed as Ig-MPGN, because the C3 intensity of the staining evaluated by IF was identical to the other immune reactants.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, because viral, bacterial, and protozoal infections are a common cause of immune-complex MPGN, it is thought that this might be a reason why MPGN is more common in developing countries (Cook and Pickering 2015 disease mechanism, recent studies have shown mutations also affecting the alternative pathway (AP) regulatory proteins and C3 nephritic factor (C3NeF)an autoantibody that stabilizes the AP C3 convertase. These findings suggest that the alternative pathway itself could also play an active role in MPGN type I pathogenesis (Alfandary and Davidovits 2015;Dragon-Durey 2004;Iatropoulos et al 2016;Leroy et al 2011;Servais et al 2012;Radhakrishnan et al 2012).…”
Section: Epidemiologymentioning
confidence: 81%
“…Genetic causes of complement abnormalities, such as CFH and CFI mutations, have been described in various case reports. Further, a genetic abnormality in the AP was identified in more than 50% of a French cohort with MPGN type I (Servais et al 2011;Servais et al 2012;Radhakrishnan et al 2012;Alfandary and Davidovits 2015;Dragon-Durey 2004). Further studies are required to determine the extent to which AP dysregulation contributes to immune-complex-mediated MPGN.…”
Section: Epidemiologymentioning
confidence: 99%